The main mediating lipid species in cholesterol-induced colorectal cancer risk - Wang, Yuanyuan; Wang, Tiantian; Shen, Xinru; Zhu, Zhitu (Frontiers in Nutrition, 2025)
BackgroundResearch has indicated that both total cholesterol (TC) and low-density lipoprotein (LDL) cholesterol levels may impact the risk of colorectal cancer (CRC). However, as TC and LDL cholesterol consist of multiple lipid species, it remains uncertain which specific species contribute to this risk. Therefore, this study plans to search for the major lipid species that influence the risk of CRC.MethodsInitially, a two-sample Mendelian randomization analyses was employed to examine the association between 179 lipid levels and the risk of CRC. Subsequent to this, a meta-analysis was conducted on the results of Mendelian randomization analyses in four CRC cohorts to further determine the relationship between the implicated lipids and CRC risk. Reverse Mendelian randomization was utilized to investigate the potential reverse causal relationship between the relevant lipids and CRC. Lastly, a two-step Mendelian randomization analysis was employed to assess whether the associated lipids acted as mediators in the relationship between TC and LDL cholesterol levels and CRC risk.ResultsOur study identified five lipid levels across multiple cohorts that were significantly associated with the risk of CRC. Meta-analysis results indicated a positive correlation between sterol ester (27:1/14:0) and sterol ester (27:1/16:0) levels and CRC risk (p < 0.05), with no evidence of reverse causality. Furthermore, sterol ester (27:1/14:0) and sterol ester (27:1/16:0) were found to mediate the relationship between TC and LDL cholesterol levels and the risk of CRC. Specifically, sterol ester (27:1/14:0) accounted for 87.9 and 93.3% of the effects of TC and LDL cholesterol on CRC risk, while sterol ester (27:1/16:0) mediated 44.3 and 44.6% of these effects, respectively.ConclusionSterol esters (27:1/14:0) and (27:1/16:0) are significant lipids that influence the risk of CRC and act as mediators of TC and LDL cholesterol increasing the risk of CRC.